Factors Affecting Inflation 4 Cities in North Sumatra Province - Darwin Damanik; Pawer Darasa Panjaitan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to determine the effect of government expenditure variables, Gross Regional Domestic Product, and District/City Minimum Wage on inflation in 4 CPI cities of North Sumatra, namely, Medan, Pematangsiantar, Sibolga, and Padangsidempuan for the period 2016-2020. The method used in this study is quantitative and uses a panel data regression model. The data used is secondary data obtained from the Central Statistics Agency (BPS). The results showed that the variables of government expenditure and the district/city minimum wage had a positive and insignificant effect on inflation in 4 CPI cities of North Sumatra Province. Meanwhile, the Gross Regional Domestic Product per capita variable has a negative and significant effect on inflation in 4 CPI Cities in North Sumatra Province.